2003
DOI: 10.1177/02698811030173014
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Acute Metabolic Stress on the Peripheral Vasopressinergic System in Schizophrenia

Abstract: Although both vasopressin and stress have been implicated in the course of schizophrenia, it is unknown whether schizophrenic patients have altered stress-induced function of the vasopressinergic system. We examined the effects of acute metabolic stress induced by pharmacological doses (40 mg/kg) of 2-deoxyglucose (2DG) on plasma concentrations of vasopressin in 13 patients with schizophrenia (with no history of polydipsia and hyponatremia) and 12 healthy control subjects. Baseline vasopressin levels were lowe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
2

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 66 publications
0
13
2
Order By: Relevance
“…Schizotypal personality disorder patients also show greater amphetamine-induced DA release than controls, though less than that seen in acute schizophrenic patients (Abi-Dargham et al, 2004). A metabolic stressor, 2-deoxy-glucose, induced significantly larger increases in plasma HVA in schizophrenic patients than controls (Elman et al, 2003). Interestingly, the same stressor produced HVA elevation in schizotypal personality disorder patients only equivalent to controls, along with a blunted cortisol response, possibly indicating that these patients possess a buffering mechanism against hypothalamic-pituitary-adrenal axis stress activation .…”
Section: Introductionmentioning
confidence: 82%
“…Schizotypal personality disorder patients also show greater amphetamine-induced DA release than controls, though less than that seen in acute schizophrenic patients (Abi-Dargham et al, 2004). A metabolic stressor, 2-deoxy-glucose, induced significantly larger increases in plasma HVA in schizophrenic patients than controls (Elman et al, 2003). Interestingly, the same stressor produced HVA elevation in schizotypal personality disorder patients only equivalent to controls, along with a blunted cortisol response, possibly indicating that these patients possess a buffering mechanism against hypothalamic-pituitary-adrenal axis stress activation .…”
Section: Introductionmentioning
confidence: 82%
“…By contrast, plasma reelin [94] , which is involved in the migration of neurons; and adenosine deaminase activity [95] , a homeostatic modulator that affects brain DA and glutamate activities, were higher in people with Sz. It is also of note that acute metabolic stress in the brain, induced by pharmacological doses of 2-deoxyglucose (2DG), a glucoprivic agent transported across the bloodbrain barrier into brain tissue where it inhibits intracellular glucose metabolism and produces a clinical state similar to hypoglycaemia [96] , appears to affect the peripheral vesopressinergic system via the pituitaryadrenal axis [96,97] . In addition, after 2DG treatment people with Sz had higher 2DG-induced plasma adrenocorticotropic hormone levels [97] , HVA, and 5hydroxyindoleacetic acid levels [96] .…”
Section: Other Neurochemicalsmentioning
confidence: 99%
“…It is also of note that acute metabolic stress in the brain, induced by pharmacological doses of 2-deoxyglucose (2DG), a glucoprivic agent transported across the bloodbrain barrier into brain tissue where it inhibits intracellular glucose metabolism and produces a clinical state similar to hypoglycaemia [96] , appears to affect the peripheral vesopressinergic system via the pituitaryadrenal axis [96,97] . In addition, after 2DG treatment people with Sz had higher 2DG-induced plasma adrenocorticotropic hormone levels [97] , HVA, and 5hydroxyindoleacetic acid levels [96] . These data suggest that central acute metabolic stress may alter the metabolism in peripheral dopaminergic and serotonergic systems via hormones (Figure 1).…”
Section: Other Neurochemicalsmentioning
confidence: 99%
“…The physical stimuli activate the HPA axis responses mostly via corticotropin-releasing hormone (CRH), and the psychological stimuli mostly via AVP. It has also been reported that baseline plasma AVP levels were lower in schizophrenic patients, and progressively increased following acute metabolic stress like 2-deoxy-Dglucose (2DG) (Elman et al, 2003). Concomitantly, it has been found that patients with schizophrenia had higher 2DG-induced plasma homovanillic acid (HVA) and 5-hydroxyindoleacetic acid (5-HIAA) levels.…”
Section: Introductionmentioning
confidence: 99%